The Yeast Spore Wall Enables Spores to Survive Passage through the Digestive Tract of Drosophila - Coluccio, Alison E.; Rodriguez, Rachael K.; Kernan, Maurice J.; Neiman, Aaron M. (PloS one, 2008)
In nature, yeasts are subject to predation by flies of the genus Drosophila. In response to nutritional starvation Saccharomyces cerevisiae differentiates into a dormant cell type, termed a spore, which is resistant to many types of environmental stress. The stress resistance of the spore is due primarily to a spore wall that is more elaborate than the vegetative cell wall. We report here that S. cerevisiae spores survive passage through the gut of Drosophila melanogaster. Constituents of the spore wall that distinguish it from the vegetative cell wall are necessary for this resistance. Ascospores of the distantly related yeast Schizosaccharomyces pombe also display resistance to digestion by D. melanogaster. These results suggest that the primary function of the yeast ascospore is as a cell type specialized for dispersion by insect vectors.